Common Knowledge, Common Attitudes and Social Reasoning - Thomason, Richmond H. (Bulletin of the Section of Logic, 2021)
For as long as there have been theories about common knowledge, they have been exposed to a certain amount of skepticism. Recent more sophisticated arguments question whether agents can acquire common attitudes and whether they are needed in social reasoning. I argue that this skepticism arises from assumptions about practical reasoning that, considered in themselves, are at worst implausible and at best controversial. A proper approach to the acquisition of attitudes and their deployment in decision making leaves room for common attitudes. Postulating them is no worse off than similar idealizations that are usefully made in logic and economics. <input id="idg-io-safe-browsing-enabled" type="hidden" />